Hospital length of stay: is rivaroxaban associated with shorter inpatient stay compared to warfarin among patients with non-valvular atrial fibrillation?. (April 2014) - Laliberté, François; Pilon, Dominic; Raut, Monika K.; Nelson, Winnie W.; Olson, William H.; Germain, Guillaume; Schein, Jeff R.; Lefebvre, Patrick
Abstract Background: Warfarin has been the mainstay treatment for prevention of stroke among patients with non-valvular atrial fibrillation (NVAF). Unlike rivaroxaban, warfarin requires laboratory monitoring to allow the attainment of the prothrombin time (PT) international normalized ratio (INR) goal, thereby potentially prolonging a patient's hospital length of stay (LOS). Objective: To compare hospital LOS between hospitalized NVAF patients using rivaroxaban versus warfarin in a real-world setting. Methods: A retrospective claims analysis was conducted using the Premier Perspective Comparative Hospital Database from 11/2010 to 9/2012. Adult patients were included in the study if they had a hospitalization for NVAF. Patients using rivaroxaban during hospitalization were matched with up to four warfarin users by propensity score analyses. Patients who were first administered their oral anticoagulants on day 3 or later of their hospital stay were also evaluated. Comparison of hospital LOS was assessed using generalized estimating equations. Results: The characteristics of the matched cohorts were well balanced. Among the matched rivaroxaban and warfarin users (2809 and 11, 085 patients, respectively), the mean age of the cohorts was 71 years and 49% of patients were female. The average (median) hospital LOS for rivaroxaban patients was 4.46 (3) days, compared to 5.27 (4) days for the warfarin cohort. The mean difference in hospital LOS of 0.81 days (19.44 hours) was found to be significant at P < 0.001. Patients who were administered rivaroxaban on day 3 of their hospital stay or later also had a significantly lower LOS compared to warfarin users. Limitations: These included inaccuracies or omissions in diagnoses, completeness of baseline characteristics, and a study population that included patients newly initiated on and patients who continued anticoagulant therapy. Conclusion: The study sample of NVAF patients receiving rivaroxaban was associated with a significantly shorter hospital length of stay compared to the sample of patients receiving warfarin.